UTILITY OF HBME1 IMMUNOSTAIN IN DIFFERENTIATING REACTIVE MESOTHELIAL CELLS LESIONS FROM MALIGNANT EPITHELIAL CELLS LESIONS IN SEROUS EFFUSIONS - Raut, Sonal; Gujar, Reetesh Kumar; Ali, Mustafa; Bhopalwala Ali, Fatima (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Parietal and the visceral layers of the mesothelium are separated by a thin layer of lubricating fluid and are made up of a single layer of flat cells. The three body cavities pleura, peritoneum, and pericardium are lined by mesothelium. The collection of fluid inside these cavities is called an effusion and may be due to a variety of inflammatory, infective, and neoplastic causes and often causes reactive mesothelial cells hyperplasia that sometimes is very hard to differentiate from malignant epithelial cells in cytopathological examinations of these fluids. Methods: We studied the utility of the Human Battifora Mesothelial Epitope-1 (HBME1) immunostain to differentiate these conditions. All the fluids from various effusions collected at the department of pathology, at a tertiary care institute in Lucknow were included in the study. Detailed history, examination findings, blood investigations, imaging findings, and histopathology reports were also noted. Fluids that showed reactive mesothelial hyperplasia and/or malignant epithelial cells on microscopic examination were further analyzed by the application of HBME1 on the cell block. Results: A total of 50 fluids were studied finally including 30 cases from the positive malignant cells group and 20 cases from the reactive mesothelial cells group. Out of 30 cases included in the malignant cells group, 16 cases (53.33%) were immunoreactive for HBME1, and out of the 20 cases included in the reactive mesothelial cell group, 18 cases (90%) showed immunoreactivity for HBME1. Conclusion: Observing this we can conclude that HBME1 immunoreactivity was significantly associated with the presence of reactive mesothelial cells compared to the malignant cells group.